Evaluation the Role of Interleukin-8 and Interleukin-10 in Myocardial Infarction Patients in Al- Najaf City - Wijdan Dhaidan Shnain Al-Abbas (University of Thi-Qar Journal of Science, 2019)
This study conducted to evaluate the interleukin-8 and interleukin- 10 level in hypertension and myocardial infarction patients in the period from March to December 2018 by using ELISA technique. A total of thirty three (33) patients from which (5 women and 8 men) with MI and (7 women and 4 men) with hypertension and a total of 19 (7 women and 12 men) healthy individuals were considered as control group. Resulting in, the mean of interleukin-8 level of hypertension and myocardial infarction patients (416.6 pg/ml) and (433.2pg/ml) respectively, with significant elevation comparing with non hypertension (292.03 pg/ml), non myocardial patients (378.9 pg/ml) and control (123.1 pg/ml), furthermore, mean of interleukin-10 level of hypertension and myocardial infarction patients (320.5pg/ml) and (102.9 pg/ml) respectively, with significantly different compared with non patients and control, where show significant increase mean of interleukin-10 level of hypertension compared with non hypertension patients (260.5 pg/ml) and control (129.4 pg/ml), also show a significant decline mean of interleukin-10 level for myocardial in comparison with non myocardial patients (146.3 pg/ml) and control (129.4 pg/ml). Concluded that  interleukin-8 (pro and anti- inflammatory) significantly raised in hypertension and myocardial infarction in coronary artery patients, in contrast, this result observed decrease production of anti-inflammatory cytokines IL-10 in myocardial patients.